A relational approach to organised crime - Campana, Paolo (Trends in organized crime, 2024)
This is an introduction to the articles submitted to the special issue of Trends in Organized Crime on ‘Crime and Networks’. The aim of this special issue is to advance our relational understanding of organised crime, gangs and crime more generally by presenting six works exploring a diverse set of questions related to organised crime, street gangs, outlaw motorcycle gangs, money laundering and groups operating in cyberspace.